Binder′s syndrome (maxillonasal dysplasia) different treatment modalities: Our experience - Deshpande, Sanjeev N.; Juneja, Manpreet H. (Indian Journal of Plastic Surgery, 2012)
Aim: Being an uncommon congenital condition, the treatment modalities of maxillonasal dysplasia are not clearly defined. Our aim is to discuss the availability and utility of various treatment options to achieve optimum results. In patients with Binder′s syndrome, the midface appears flattened, the columella is short and the upper lip slants backwards. Materials and Methods: We report here 15 patients with Binder′s syndrome who were operated over a period of 5 years. Different treatment options in the form of correction of the depressed nasal dorsum and maxillary hypoplasia with split cranial bone graft or synthetic materials such as high-density porous polyethylene implant were used. Two patients with Angle class III malocclusion underwent a Le Fort I osteotomy for maxillary advancement. The patients were followed over a period of 3 years. Results: We achieved a reasonable augmentation of the nose and the maxilla in our patients. We faced complications in two of our patients; in one patient there was fracture of the dorsal nasal bone graft and the other patient had protrusion of paranasal screws into the palate, which were removed. Conclusion: In this series of cases, we were able to utilise various treatment modalities appropriately to achieve satisfactory outcome with no significant complications.
Keywords: Binder’s syndrome; maxillonasal dysplasia; split calvarial bone graft